2012
DOI: 10.1021/ac202734m
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-Visible Light (UV–Vis)-Reversible but Fluorescence-Irreversible Chemosensor for Copper in Water and Its Application in Living Cells

Abstract: An ultraviolet-visible light (UV-Vis)-reversible but fluorescence-irreversible chemosensor was developed for the detection of copper. Coordination between the probe, 2-pyridylaldehyde fluorescein hydrazone (FHP), and Cu(2+) gave a reversible UV-Vis response, Storage of the probe-Cu complex resulted in hydrolytic cleavage of the N═C bond, which released the fluorophore (ring-opened fluorescein hydrazine) and gave irreversible fluorescence. Thus, FHP becomes a multifunctional chemosensor, and its reversibility c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(49 citation statements)
references
References 58 publications
(53 reference statements)
3
46
0
Order By: Relevance
“…Compounds 183 and 184 have also been proposed as highly selective and sensitive fluorescence probes for Cu 2+ based on the Cu 2+ -promoted spirolactam ring-opening of rhodamine derivatives. 493,494 Lin's group introduced a unique strategy to design a NIR fluorochrome with the carboxylic acid-controlled fluorescence on−off switching mechanism by spirocyclization. 495 On the basis of this platform, they synthesized 185 as an NIR fluorescent probe for Cu 2+ .…”
Section: Cleavage Of Covalent Bonds By Metal Ionsmentioning
confidence: 99%
“…Compounds 183 and 184 have also been proposed as highly selective and sensitive fluorescence probes for Cu 2+ based on the Cu 2+ -promoted spirolactam ring-opening of rhodamine derivatives. 493,494 Lin's group introduced a unique strategy to design a NIR fluorochrome with the carboxylic acid-controlled fluorescence on−off switching mechanism by spirocyclization. 495 On the basis of this platform, they synthesized 185 as an NIR fluorescent probe for Cu 2+ .…”
Section: Cleavage Of Covalent Bonds By Metal Ionsmentioning
confidence: 99%
“…This was attributed to the higher chelating ability of EDTA for Cu 2+ (lgK Cu-EDTA = 18.8). Cu 2+ was removed from the surface of BSA-Cu NCs with the addition of EDTA to the system resulting in the restoration of fluorescence [34]. Hence, the BSA-Cu NCs was in the "on" state.…”
Section: Resultsmentioning
confidence: 99%
“…2 It has been found that the alteration in the cellular homeostasis of copper is connected to serious neurodegenerative diseases, including Menkes disorder, Wilson's disease, familial amytropic lateral sclerosis, and Alzheimer's disease. 3,4 Thus, chemosensors for copper ions, [5][6][7][8] especially those used in environment friendly aqueous solvents with sensitive and fast fluorescent response signals, [9][10][11] have received much attention in recent years. Histidine (His) not only plays a key role in the formation of the myelin sheath, the protective barrier that surrounds neural cells and supports the transmission of brain signals to different parts of the body, but also participates in the detoxification of heavy metals and other cellular debris for elimination through the liver and kidneys.…”
Section: Introductionmentioning
confidence: 99%